(untitled) - Acemoglu, Daron (Boston, 2016)
Taking a fresh approach, the authors use the themes of optimization, equilibrium and empiricism to illustrate the power of simple economic ideas, and their ability to explain, predict, and improve what happens in the world. Each chapter begins with an empirical question that is later answered using data in the Evidence-Based Economics feature. As a result of the text’s practical emphasis, students will learn to apply economic principles to guide the decisions they make in their own lives.
Keywords: Economics,Kinh tế học